2005
DOI: 10.1097/01.mlg.0000161338.54515.b1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lymph Node Metastasis in the Treatment of Squamous Cell Carcinoma of the Oral Cavity, Oropharynx, Larynx, and Hypopharynx: N0 Versus N+

Abstract: Lymph node metastasis significantly and negatively affects DSS in patients with SCCA of the OC, OP, LX and HP. The rate of occult neck disease (pN+) in N0 patients receiving meticulous workup is low. When present, it produces DSS rates similar to those found in N+ patients. In the study series, there was decreased survival in patients older than 65 years of age, in patients with advanced tumor (T, N, TN), and in patients with recurrent disease. None of the four current approaches to treatment of the N0 neck pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
206
1
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(225 citation statements)
references
References 18 publications
10
206
1
8
Order By: Relevance
“…Our results of combined treatment in patients with laryngeal cancer do not differ from the outcomes that have been obtained over a period of 30 years in different cancer centres [6,7,11,14,15,18,20,21,22,23,24,25,26,27,28,29,30,31].…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Our results of combined treatment in patients with laryngeal cancer do not differ from the outcomes that have been obtained over a period of 30 years in different cancer centres [6,7,11,14,15,18,20,21,22,23,24,25,26,27,28,29,30,31].…”
Section: Discussioncontrasting
confidence: 45%
“…Literature reports highlight the effect of this factor on the prognosis in patients with head and neck cancers [16,28,32,33,34,36]. Layland et al [28] observed reduced survival in patients with N+ disease compared to N0. Wang et al [38] found a significant decrease of long-lasting LC from 88% for N0 to 49% if the postoperative material contained more than 3 metastatic lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of lymph node metastases frequently was common and occurred in 50% to 80% of patients with nasopharyngeal or oropharyngeal carcinoma. 23,24 Patients with stage II WR-DLBCL may have their disease encompassed in 1 radiation field and should be approached in a manner similar to that for patients with stage I disease, as suggested by Armitage. 25 Moreover, patients with WR-DLBCL tend to have a lower tumor burden, including a lower frequency of elevated LDH or elevated b2M levels, fewer B symptoms, and less involvement of the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…3 When occult metastases are present, overall survival drops to levels found in patients who present with node-positive necks at diagnosis, irrespective of the primary treatment modality employed. 4 Failure in the neck after definitive neck treatment offers a distinctively poorer prognosis than local recurrences. 5 In a tumor registry based study by Deschamps et al, out of 1291 patients of head and neck cancer treated between 1998 and 2007 there were 224 recurrences of which 47 isolated neck recurrences.…”
Section: Neck Nodes Are Important Prognostic Factor Affecting Survivalmentioning
confidence: 99%